Social psychology - Aronson, Elliot; Wilson, Timothy D.; Akert, Robin M. (England : Pearson, 2014)
This comprehensive introduction to social psychology explores self, attitudes, socialization, communication, interpersonal attraction and relationships, and personality and social structure.
-- Expanded Table of Contents -- Preface -- 1. Introduction to Social Psychology -- 2. Research Methods in Social Psychology -- 3. Socialization Through the Life Course -- 4. Self and Self-Presentation -- 5. Emotions -- 6. Social Perception and Cognition -- 7. Attitudes -- 8. Symbolic Communication and Language -- 9. Social Influence and Persuasion -- 10. Altruism and Prosocial Behavior -- 11. Aggression -- 12. Interpersonal Attraction and Relationships -- 13. Understanding Groups -- 14. Group Processes -- 15. Social Structure and Personality -- 16. Deviant Behavior and Social Reaction -- 17. Collective Behavior and Social Movements -- Glossary -- References -- Index.
Includes bibliographical references (pages 518-521) and index.
Keywords: Social psychology